Optimization of Digital Image Processing Method to Improve Smoke Opacity Meter Accuracy - Dwi Sudarno Putra; Donny Fernandez; - Wagino (Society of Visual Informatics, 2018)
One of the parameters of exhaust emission testing on diesel engines is the level of smoke opacity. If the opacity is high then the emission quality is bad. The instrument for measuring smoke opacity is called Smoke Opacity Meter. The commonly used basic concept to measure smoke density is by utilizing a light sensor (optical sensor). Development of Smoke Opacity Meter applies the concept of Digital Image Processing. Even though it has initially begun, the measurement result is yet as perfect as Optical Sensor Concept. Therefore, this paper describes on how to implement the Digital Image Processing Method in processing the smoke opacity video data.